Variability of the number of curves considering different data sources in cultivated areas in Southeastern Spain - Juan Manuel García-Guerrero; Juan Tomás García; Manuel Alcaraz-Aparicio; Luis Gerardo Castillo; Luis Altarejos-García; Jose María Carrilllo (Ingeniería del Agua)
The evaluation of the infiltration is essential to estimate the surface runoff after a rainfall event. The curve number (CN) method is one of the most widely used to estimate the amount of runoff, in this work, the curve number has been calculated in two watersheds located in the Southeastern Spain, considering the land uses of the Corine Land Cover and SIOSE projects along different periods, and the soil classifications of the LUCDEME project and the MAGNA geological map. The results obtained using Geographical Information Systems show that, although the land uses change the CN, the highest variation is due to the consideration of the hydrological group of the soil as type B or C. Continuous simulation of soil moisture, in plots with specific crops and irrigation, over the study period has resulted in antecedent moisture values close to the CN II hypothesis during considerable periods of the year.